Reintroducing serum FSH measurement during ovarian stimulation for ART. Issue 3 (March 2022) - Lawrenz, Barbara; Melado, Laura; Digma, Shieryl; Sibal, Junard; Coughlan, Carol; Andersen, Claus Yding; Fatemi, Human M.
Abstract: Research question: What is the impact of systemic FSH concentrations during ovarian stimulation for IVF/intracytoplasmic sperm injection on systemic progesterone concentrations in the late follicular phase? Design: Post-hoc analysis of a previously performed randomized controlled trial (RCT) performed between November 2017 and February 2020 in a tertiary IVF centre. The RCT included patients with infertility undergoing ovarian stimulation in a gonadotrophin-releasing hormone (GnRH) antagonist protocol. The GnRH antagonist was administered at 08:00 h and recombinant FSH at 20:00 h. Ultrasound and blood tests were performed 3–5 h after the GnRH antagonist. Results: The subgroup analysis comprised 105 patients. Systemic FSH concentrations increased from Day 2/3 until initiation of GnRH antagonist and remained constant until the day of trigger (DoT). The total group was split according to the median FSH DoT concentration (12.95 IU/l; Group A <12.95 IU/l; Group B ≥12.95 IU/l). Significant differences, with the higher concentrations in Group B, were found for: systemic FSH concentration on Day 2/3 ( P = 0.04), total gonadotrophin dosage ( P = 0.03), progesterone on DoT ( P = 0.001) and progesterone per follicle ( P = 0.004). In the total group, systemic DoT FSH concentration was statistically significantly positively correlated with the DoT progesterone concentration and the ratio of progesterone per follicle (ρ = 0.37 and 0.38, respectively, both P < 0.001). No significant correlations were seen between the systemic DoT FSH concentration and the number of retrieved oocytes. Conclusion: While ovarian response seems to be independent from the systemic FSH concentrations on the DoT, high concentrations of circulatory FSH augment the production of progesterone.